Building Customer Relationships at Larut Coffee - Tasya; Seny Luhriyani; Geminastiti Sakkir (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2023)
Tasya, 2023. Building Customer Relationships at Larut Coffee. Department of English, Faculty of Language and Literature. Universitas Negeri Makassar (supervised by Seny Luhriani, S.Kom., M.T and Dr. Geminastiti Sakkir, S.Pd., M.PdBuilding relationships with customers is one of the company's strategies to maintain good relationships with customers which aims to retain existing customers to make repeat purchases. The purpose of this writing is to find out how employees maintain customer loyalty in building relationships and find out the obstacles experienced by customer service. This study uses data analysis which is processed through three analysis items, namely reduced data, presented data and making conclusions. In this study, the object of research were 13 customers and employees of Larut Coffee. The results of the study show that there is a good relationship between customers and employees seen from customer loyalty to Larut Coffee, so that the problems experienced by customer service can be handled properly by employees. This can be seen from customer loyalty and employee performance in building relationships.Keywords: Building relationships, customer loyalty, customer service.